Personal informatics for everyday life: How users without prior self-tracking experience engage with personal data. Issue 94 (October 2016) - Rapp, Amon; Cena, Federica
Abstract: The spreading of devices and applications allowing people to collect personal information opens new opportunities for Personal Informatics. Although many of these tools are already effectively used by motivated people to gain self-knowledge and produce change in their behaviors, there is a great number of users that are potentially interested in Personal Informatics but do not know of its potentialities and criticalities. In order to investigate how users perceive and use self-tracking tools in everyday life, we conducted a diary study, requiring fourteen participants with no previous experience in Personal Informatics to use a variety of trackers. We discovered that they use and perceive these technologies differently from the ones experienced in self-tracking. Participants considered the act of collecting personal information burdensome, with no beneficial reward. We also uncovered a series of problems that they experienced while tracking, managing, visualizing, and using their data. Among them we found that the lack of suggestions on using data and the excess of abstract visualization in the apps prevented users to gain useful insights. As a result, their interest in self-tracking soon faded, despite their initial curiosity in exploring and "playing" with their data. Starting from the findings of this study, we identified seven design strategies to better Personal Informatics tools, supported by literature and examples that draw from different research fields, from tangible interfaces, to virtual environments and video games. These strategies are primarily addressed to satisfy the inexperienced users' needs, but their applicability can be reasonably extended to all the individuals curious and interested in Personal Informatics. Highlights: We describe how new users curious in PI (naïve users) are different from experienced users. We explore how naïve users use, perceive, and integrate in their daily practices PI tools. We point to the barriers that naïve users may encounter when using PI tools. We identify a new tracking style characterized by discovery and playfulness. We propose new design strategies primarily addressed to satisfy naïve users' needs.